Reaction of Sao Paulo stock exchange corporative events: a test of the Efficient Market Hypothesis Análise empírica da reação do mercado de capitais brasileiro a eventos corporativos: teste conjunto da Hipótese de Eficiência do Mercado - Marcos Antônio de Camargos (REGE Revista de Gestão, 2006)
The Efficient Market Hypothesis, defined by Fama (1970 and 1991), in the moderate version, postulates an instantaneous and precise adjustment by the market for any relevant information announced by participating companies. An analysis was made of the reaction of Sao Paulo Stock Exchange to abnormal returns around the time of announcement of the three specific corporate events of fusions and acquisitions, issuance of American Depositary Receipts and adherence to the Different Levels of Corporate Governance, in order to identify if the market was efficient according to the moderate Hypothesis. An Event Study collected data, between 1992 e 2004 of company stocks on the Exchange, for analysis of preferred stocks at times around all three types of these event announcements and for common stock analysis only at times around last type of event. Announcements of all the three types of events were shown to provide information relevant to market stock pricing. Exchange market reactions were found however only for fusions and acquisitions and adherence to the Different Levels of Corporate Governance but not for American Depositary Receipt. Because this market reacted to only two of the three types of events cited in the Hypothesis, it was therefore considered not to be efficient according to the moderate version of the Efficient Market Hypothesis. A Hipótese de Eficiência do Mercado, definida por Fama (1970, 1991), pressupõe, em sua forma semiforte, que o mercado faz ajustes instantâneos e precisos de qualquer informação relevante que seja divulgada pelas empresas que dele participam. Neste artigo, fez-se uma análise da eficiência do mercado brasileiro por meio do estudo do comportamento dos retornos anormais acumulados em períodos próximos à divulgação de três eventos corporativos - fusões e aquisições, lançamento de American Depositary Receipts e adesão aos Níveis Diferenciados de Governança Corporativa -, visando identificar se o mercado comportou-se de maneira eficiente no que se refere à forma semiforte. Mediante um Estudo de Evento, foram realizados testes com ações preferenciais de firmas negociadas na Bovespa para os três eventos e também com ações ordinárias para o último, ocorridos entre 1992 e 2004. As principais conclusões foram: i) os anúncios de F&As, lançamento de ADRs e adesão aos NDGC (ON) apresentam conteúdo informacional relevante para a precificação das ações no mercado; e ii) o mercado brasileiro não se comportou de maneira eficiente na forma semiforte, pois a HEM não foi atestada em conjunto para os três eventos estudados, confirmando-se somente para os anúncios de F&As e adesão aos NDGC.